APLIKASI VARIASI LATIHAN DRILL GAMES DALAM PENINGKATAN DAYA TAHAN DAN KETERAMPILAN MENGGIRING BOLA - Hulfian, Lalu (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
Dribbling is one of the most important skill factors to be mastered by a player in order to play well. With good herding skills, the team will be more in control of the game, the game tactics will go well, the player easily creates scoring opportunities, and players will have high confidence in the game. Thus, critical success factors in the form of techniques, tactics and mental can be achieved. Many training methods that can be used to train dribbling skills. One of them is drill games. Drill games is a method of training in the form of a game that is done repeatedly so that the response becomes very strong and not easy to forget and to happen otomasisi movement with the aim to strengthen an association or refine a skill to become permanent. Because this exercise is done repeatedly and in the form of games, then the fourth factor to achieve the achievement of physical condition of endurance can also increase. This research uses quasi-experimental method because the selection of saampel using population study technique is taking all the population into sample because the population number is relatively small. The research design used was Non Randomized control group pre test post test design. Sample 18 was divided into 2 groups, ie 9 samples to the control group and 9 samples into treatments. The tests performed are a bleep test for endurance and dribbling tests. From the calculation of the analysis obtained normal and homogeneous distribution data. From the data analysis using t test statistic, the result of the treatment group for t resilience is 3.265 and for t counting skill is 5,040. When compared with t table at 5% significant level N = 9 equal to 1.860 then t count> t table so H0 is rejected and H1 accepted which means there is increasing endurance and dribbling skill in soccer game at student of SSB Montong Gading. The conclusion of this study is that drill games drill programs have a significant effect on endurance and dribbling skills and there are different influences from both groups where the dribbling skills experience greater improvement